Online learning: strategies, budgets, and procurements - Bluem, Matt (Henry Stewart Talks, 2024)
Saint Mary’s University of Minnesota, Online education, Budgeting, Procurement, Internal production vs. acquisition, AI, Curriculum design, Accessibility